2017
DOI: 10.1007/s10548-017-0613-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Attentional Switching Between Pain and a Visual Illusion Task: A Laser Evoked Potential Study

Abstract: Previous studies demonstrated that pain induced by a noxious stimulus during a distraction task is affected by both stimulus-driven and goal-directed processes which interact and change over time. The purpose of this exploratory study was to analyse associations of aspects of subjective pain experience and engagement with the distracting task with attention-sensitive components of noxious laser-evoked potentials (LEPs) on a single-trial basis. A laser heat stimulus was applied to the dorsum of the left hand wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Different results were found by Stancak et al., who compared 2 counterbalanced conditions in 24 adults with acute pain: distraction and focusing on the pain. In the distraction condition, the participants were asked to count the figures contained in the Rubin vase optical illusion, while pain was induced by laser pulses on one hand.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Different results were found by Stancak et al., who compared 2 counterbalanced conditions in 24 adults with acute pain: distraction and focusing on the pain. In the distraction condition, the participants were asked to count the figures contained in the Rubin vase optical illusion, while pain was induced by laser pulses on one hand.…”
Section: Resultsmentioning
confidence: 71%
“…However, 2 studies in adults presented a sample of 3 and 8 subjects, and a third study did not present positive results in pain reduction. Nevertheless, in this last study, the tendency was for the distraction group to exhibit less pain than the control group; therefore, with a larger sample size it could have reached statistical significance. As a result, the level of evidence is low, and the results have a high risk of bias and provide insufficient evidence to evaluate the effect of distraction tasks in pain‐free adults who use the sense of sight.…”
Section: Discussionmentioning
confidence: 67%
“…P2 is believed to reflect the post-synaptic activity of a specific neural process, and it represents aspects of higher-order perceptual processing, modulated by attention, linguistic contextual information, memory, and repetition effects (Liu et al, 2014 ). The exact function and neural source of the P2 component are not yet known, but some evidence has indicated that P2 may reflect general neural processes that occur when a visual (or other sensory) input is compared with an internal representation or expectation in the memory or language cortex (Stancak et al, 2018 ). Therefore, the larger amplitude of the P2 ERP component in Go trials may reflect the improved pre-attention brain function produced by caffeine administration after TSD.…”
Section: Discussionmentioning
confidence: 99%